HUMANISTIC COMMUNICATION APPROACH IN THE BROADCAST OF DA'WAH HIKMAH PAGI ON RADIO REPUBLIK INDONESIA (RRI) BANDAR LAMPUNG - Rosalina, Emilia; Purnama, Fadhli (STAI Darul Qalam Tangerang, 2023)
A humanistic approach is an approach that pays attention to humanity. Do not think of it as an object that records a set of knowledge. Humanistics emphasizes the importance of preserving human existence, in the sense of helping human beings to be more humane, more cultured, as whole human beings. Based on the problems raised, researchers want to know more about the Humanistic Communication Approach of the Da'wah broadcast